Perkembangan Teknologi Panen dan Kelembagaan Panen pada Usahatani Padi - Fatmawaty, A. St; Bijaksana, Arif; Setiawan, Reza (JNSTA ADPERTISI JOURNAL, 2023)
One of the villages that applies technology in rice farming is Maccini Baji Village, Batang Sub-district. The tools and machinery used are tractors and combine harvesters. Agricultural tools and machinery used by farmers come from government assistance which is managed together through farmer groups. The research objectives were to describe the development of rice harvesting technology and analyze institutional changes in rice farming harvesting as a result of technological developments. This research was conducted from February to March 2022. The research location was in Maccini Baji Village, Batang District, Jeneponto Regency. The study population was 925 people and a sample of 16 people. The data analysis used was qualitative descriptive analysis. The results of the study are the development of rice harvesting technology in Maccini Baji Village starting from the use of harvesting tools such as ani - ani, sickle, and gebot while the machines used are thresher and combine harvester. This condition can be seen from the decreasing employment opportunities of traditional harvest laborers, decreasing income, and the increasing difficulty of finding harvest laborers due to changing professions. This results in narrower social interactions in harvesting institutions in Maccin Baji Village, greater social inequality due to the response of farmers who are more rational in making decisions regarding the efficiency and effectiveness of their paddy farms.